PETROGENESIS AND TECTONO-MAGMATIC SIGNIFICANCE OF THE ALBANIDE - HELLENIDE SUBPELAGONIAN OPHIOLITES - Saccani, Emilio; Beccaluva, Luigi; Coltorti, Massimo; Siena, Franca (Ofioliti, 2004)
The Mirdita-Subpelagonian ophiolites of the Albanide-Hellenide orogen are parts of a continuous belt extending from the former Yugoslavia to Greece, and share common geological, litho-stratigraphical, geochemical, and metallogenic features.In the Albanian sector, two distinct ophiolitic belts can be clearly identified: the Western Belt, mainly composed of mid-ocean ridge (MORB) ophiolites, and the Eastern Belt characterized by supra-subduction zone (SSZ) ophiolites with prevalent island arc tholeiitic (IAT) and minor boninitic affinity. In the easternmost border of the Western Belt (Central Mirdita), a transitional zone with MORB/IAT intermediate basalts and boninitic dykes also occur.In the Greek sector, a definite distinction into two ophiolitic belts cannot be made, and MORB-type ophiolites (western type) are subordinate, being represented only by the intrusive and lower volcanic sequences of the Pindos Massif. By contrast, SSZ- ophiolites (eastern type) are predominant and well-represented by the IAT and boninitic sequences of the Vourinos Massif, as well as by MORB/IAT intermediate basaltic-andesitic suites and boninites of the upper part of the Pindos volcanic sequence.Petrological and geochemical modelling suggest that the different Albanide -Hellenide ophiolitic sequences originated from distinctly different parental magmas by partial melting of mantle sources progressively depleted by previous melt extractions. MORB may have derived from 10 - 20% partial melting of an undepleted lherzolitic source, while MORB/IAT intermediate basalts may have generated by ca. 10% of H2O-assisted partial melting of a cpx-poor lherzolite that had previously experienced MORB extraction. IAT magmas and boninites may, in turn, have derived from 10 – 20 % and ca. 30% partial melting of the same source, variably enriched by subduction-derived fluids and related incompatible elements.The favoured tectono-magmatic model for the genesis of the Albanide-Hellenide ophiolites implies a low plate-convergence velocity with: 1) intra-oceanic subduction within a pristine MORB lithosphere, resulting in SSZ magmatism with IAT affinity, and generation of a nascent arc by nearly open-system supply of undifferentiated basalts (sheeted dyke complexes); 2) progressive slab sinking and retreat coupled with mantle diapirism and extension from the arc axis to the forearc region, with generation of boninites and/or very low-Ti tholeiites from depleted sub-arc sources, leaving highly depleted harzburgitic residua; 3) contemporaneous generation at the spreading axis of IAT/MORB intermediate basalts resulting from the interference of MORB-source diapirs with suprasubduction mantle sources; 4) convergence processes leading to obduction of large and relatively intact lithospheric sections of SSZ ophiolites onto the Pelagonian continental margin, often with the interposition of metamorphic soles. The latter have prevalent MORB affinity and represent relics of the pristine MORB lithosphere overthrust by the still hot ophiolitic slab.